Effect of acute caffeine intake on maximal aerobic speed in university soccer players assessed by the 30-15 intermittent fitness test - García-Chaves, D. C.; Fernandez Zapata, J. P.; Oyaga Álvarez, T.; Ortiz Escobar, N.; Villegas Mazo, A.; Corredor-Serrano, L. F. (Sports, 2026)
The aim of this study was to analyze the effect of acute caffeine intake on maximal aerobic speed (MAS) assessed using the 30-15 Intermittent Fitness Test (IFT) in university soccer players. An experimental, randomized, double-blind, crossover design was employed, involving 26 male university team players (n = 26). Each participant completed the test under two conditions: caffeine supplementation (220 mg; 2.85 ± 0.27 mg/kg, range 2.60-3.16 mg/kg) and placebo, separated by a 72 h washout period. The final running speed achieved (VIFT) was used as an estimator of MAS. Statistical analysis included descriptive statistics, normality testing, and paired Student`s t-test, with a significance level set at p < 0.05. The results revealed a significant improvement in VIFT under the caffeine condition (19.94 ± 1.67 km/h) compared with placebo (18.72 ± 1.50 km/h), with a mean difference of 1.22 km/h (6.5%) and a large effect size (dz = 1.24; p < 0.001). It is concluded that acute caffeine intake was associated with a significant improvement in intermittent aerobic performance in university soccer players under the conditions of the present study, suggesting that caffeine may represent a potentially useful strategy in similar applied contexts.